Coronary Physiology Derived from Invasive Angiography: Will it be a Game Changer? - Lavinia Gabara; Jonathan Hinton; Julian Gunn; Paul D Morris; Nick Curzen (Interventional Cardiology: Reviews, Research, Resources)
There is a large body of evidence suggesting that having knowledge of the presence and extent of coronary atheroma and whether it is causing downstream myocardial ischaemia facilitates optimal diagnosis and management for patients presenting with chest pain. Despite this, the use of coronary pressure wire in routine practice is surprisingly low and routine assessment of all diseased vessels before making a bespoke management plan is rare. The advent of angiogram-derived models of physiology could change diagnostic practice completely. By offering routine assessment of the physiology of all the major epicardial coronary vessels, angiogram-derived physiology has the potential to radically modify current practice by facilitating more accurate patient-level, vessel-level, and even lesion-level decision-making. In this article, the authors review the current state of angiogram-derived physiology and speculate on its potential impact on clinical practice.